Analisis Kelayakan Usaha Burger pada UMKM Burger Pelangi di Payakumang Kabupaten Ketapang - Putri Nuraini; Irfan Cholid; Assrorudin Assrorudin; Nurimansyah Nurimansyah; Rois Indriawan (Journal of Applied Accounting, 2026)
This study aims to analyze the business feasibility of Burger Pelangi MSME located in Payakumang, Ketapang Regency. The research employed a descriptive method using a mixed-method approach, combining quantitative and qualitative data. Data were collected through observation, interviews, and documentation. The analysis included operational costs, Cost Of Good Manufactured (COGM), revenue, profit, Break Even Point (BEP), Revenue Cost Ratio (R/C Ratio), and Benefit Cost Ratio (B/C Ratio). The results showed that the total operational cost of the business was IDR 3,812,028 per month, with a production volume of 540 products and a production cost of IDR 7,059 per product. The total monthly revenue reached IDR 5,940,000, generating a net profit of IDR 2,127,972 per month. Financial analysis indicated a BEP value of 122 products or IDR 1,342,000, an R/C Ratio value of 1.56, and a B/C Ratio value of 0.56. These findings indicate that Burger Pelangi MSME is still profitable, feasible to operate, and has the potential for further development in the future. Keywords:  Business feasibility analysis, MSMEs, burger, financial aspects, business profit